Empowerment Of Generation “Z” Become A Cadre Movement Of Religious Activities In Gayaman Village Post Pandemic - Al Mubarok, Ahmad Aly Syukron Aziz; Mubarok, M. Wildanil; Mufaricha, Lilis (Proceedings of Annual Conference on Community Engagement, 2022)
After the Covid 19 pandemic, it seems that the influence of social media and digital literacy has begun to sue about the importance of a social activity for the existence of the life of Generation Z today. The number of religious activities in the community is not accompanied by regeneration of cadres, so that every religious activity carried out in Gayaman Village is dominated by the elderly. The absence of a cadre forum for children and adolescents in terms of religion is one of the obstacles for the Gayaman Village community. The purpose of the service is for Generation Z to be active in religious activities in the village. Participatory Action Research (PAR) approach through the practice of adhan and Iqamah. The results of the changes that occurred in Gayaman Village Generation Z appeared to carry out the call to prayer and iqamah in mosques and prayer rooms.